Employment Outcomes of Information Systems Graduates: A Correlation Study on Job Search Timing, Income, and Institutional Influence - Ghea Sekar Palupi; Choirotus Sa’adah; Ardhini Warih Utami (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study examines the correlation between various factors—such as age, job waiting time, and initial salary—among alumni of the Information Systems program at the State University of Surabaya (UNESA) who graduated between 2022 and 2024. By analysing alumni tracer data, this research aims to uncover how these variables influence early career success and progression, offering insights into the factors that shape graduates' job market experiences. Key areas of focus include the relationship between alumni age and job search duration, the impact of job waiting time on starting salary, and how continuous skill development contributes to career advancement. Additionally, the study explores how initial salary correlates with job satisfaction, providing a deeper understanding of financial expectations and early career fulfilment. The findings are expected to inform UNESA's curriculum enhancements and support services by highlighting the educational experiences and career strategies that align with positive employment outcomes. Ultimately, this study aims to empower UNESA in delivering targeted alumni support and refining educational pathways that respond effectively to evolving industry demands, fostering sustainable career success and satisfaction among graduates.